(untitled) (Huellas, 2015)
The “Santa Trinidad” (Holy Trinity) Lutheran Church is located in the City of Punta Alta, in the southeast of the Province of Buenos Aires (Argentina). Despite having existed for fifty years in the city, its activity and interaction with other religious cults, with the local community and with the local management are unknown, thus hindering its contribution to local and cultural development. The general objective of this work was to acknowledge the contributions of the “Santa Trinidad” Lutheran Church to the local and cultural development of the city. The work’s methodology has been restricted to different procedures in the context of a case study - direct observation, surveys, interviews and social experimentation. The results showed that the church, despite the obstacles imposed by its doctrine to relate, openly, with the community, the other religious groups, and the local management, can contribute cultural and religious values to the local development of the city of Punta Alta.